Trade, Foreign Direct Investment and Agriculture in Developing Countries - Badu-Prah, Charlotte; Agyeiwaa-Afrane, Akua; Gidiglo, Ferguson K.; Srofenyoh, Francis Y.; Agyei-Henaku, Kofi Aaron A-O.; Djokoto, Justice Gameli (Research on World Agricultural Economy, 2023)
Agriculture continues to make significant contributions to developing countries in the presence of globalisation. Thus, international trade and foreign capital flows are important to developing countries. The authors used data on 115 developing countries from 1995 to 2020 to investigate the effect of inward and outward foreign direct investment (FDI) on trade in the agricultural sector of developing countries. Inward FDI enhanced exports, imports, and trade openness. However, outward FDI did not affect exports, imports, and trade openness. To escalate international trade in agricultural products, developing countries must continue to promote the inflow of FDI into agriculture (AIFDI). This requires paying attention to appropriate management of the macroeconomy, keeping down the inflation rate, optimising the currency exchange rate, and keeping interest rates down to boost investment among others. Whilst these would enhance AIFDI that would promote trade, these would directly promote trade. As developing countries have often suffered foreign exchange pressures, they must enhance foreign exchange receipts through increased exports. Increasing human capital can increase exports. Unlike existing studies, the authors used more current data covering many developing countries and accounted for endogeneity. ER